2020
DOI: 10.4067/s0717-92002020000300333
|View full text |Cite
|
Sign up to set email alerts
|

Seed protein profile of Pinus greggii and Pinus patula through functional genomics analysis

Abstract: The present work was carried out with the aim of analyzing and describing the seed proteome of Pinus patula and Pinus greggii. The analysis was performed using the "shotgun" ("gel-free") strategy. Proteins were extracted using the TCA/Phenol/Acetone protocol, subsequently separated by liquid chromatography and analyzed by mass spectrometry (nLC LTQ Orbitrap). Protein identification was performed by consulting the specific database for Pinus spp and functional classification taking into account the three functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Nevertheless, this discrepancy clearly illustrates the difficulty of extracting all proteins from an organ, as explained in a recent publication on this subject [ 48 ]. This technical difficulty is not limited to our study; however, we observe organ-specific protein counts quite similar to those obtained for other species: 3082 in the wood of Populus tremula [ 49 ], 1533 in the seeds of Pinus radiata [ 33 ] but only 629 in Pinus patula seeds [ 32 ]; 503, 1250 or 3000 for different stages somatic embryogenesis of Larix principis-rupprechtii [ 33 ], of Picea glauca [ 50 ] or of Quercus suber [ 51 ], respectively.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Nevertheless, this discrepancy clearly illustrates the difficulty of extracting all proteins from an organ, as explained in a recent publication on this subject [ 48 ]. This technical difficulty is not limited to our study; however, we observe organ-specific protein counts quite similar to those obtained for other species: 3082 in the wood of Populus tremula [ 49 ], 1533 in the seeds of Pinus radiata [ 33 ] but only 629 in Pinus patula seeds [ 32 ]; 503, 1250 or 3000 for different stages somatic embryogenesis of Larix principis-rupprechtii [ 33 ], of Picea glauca [ 50 ] or of Quercus suber [ 51 ], respectively.…”
Section: Discussionsupporting
confidence: 75%
“…The abundance of this protein is likely attributable to its importance in post-germination nucleic syntheses. Similarly, Alfonso et al (2020) [32] demonstrated the importance of proteins involved in oxidation-reduction reactions to seed preparation for germination. Finally, we observed much higher abundances of BP terms in the immature somatic embryo proteome than in the other organs (Table S5), likely due to the totipotent nature of this type of tissue and its involvement in organogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation